Indonesia Demographic Potential to Developing Productive Young Entrepreneur for Reinforcement the Digital Economy - Tipri Rose Kartika; Handika Dany Rahmayanti; Adryans; Trifajar Yurmama Supiyanti (International ABEC, 2022)
Indonesia is currently experiencing a demographic bonus. Indonesia's current demographic potential is very large for strengthening and developing productive and quality young entrepreneurs. Universities have abundant quality young human resources so that they deserve to be a priority for strengthening and developing productive and quality young entrepreneurs. Environmental conditions are getting worse, making environmentally friendly technology-based businesses start to emerge as a solution. The complicated polemic of plastic waste management is now a promising business potential, for example from plastic products from seaweed, cassava, and others. Environmentally friendly business is now one of the trends because the level of awareness of environmental conservation is increasing